Developing Culturally Competent Faculty: A Cognitive, Affective, and Spiritual Model - Taylor, Deborah L. (Christian higher education, 2013)
The past decade has evidenced significant dialogue on faith-based campuses about the persistent gap between the increasing ethnic diversity of the student population and that of the faculty. While campus administrators and leaders acknowledge the need to address this concern through faculty development, there is a disturbing lack of successful models for developing a culturally competent faculty. When coupled with the motivation of faith-based institutions to integrate a biblical foundation and spiritual approach to these topics, it can feel like an overwhelming task. In this article, the authors describe a faculty development pilot program that serves as a “best practices” model designed to blend the cognitive, affective, and spiritual dimensions and required faculty to engage with the complexities of diversity from multiple perspectives. The model includes several foundational elements, yet the authors believe it could be adapted to fit a variety of university contexts where cultural competency is both valued and needed.